2013
DOI: 10.2151/jmsj.2013-303
|View full text |Cite
|
Sign up to set email alerts
|

A Common Stomatal Parameter Set Used to Simulate the Energy and Water Balance over Boreal and Temperate Forests

Abstract: A parameter set expressing the potential response used to simulate evapotranspiration was inferred from pooled data of leaf-level stomatal conductance in the Far East. We used Jarvis-type parameterization, which consists of restriction terms of light, air dryness, temperature, and soil water. Two parameter sets, pooled common (PC) and within-site (WS) 273Corresponding author: Takeshi Yamazaki, Department of Geophysics, Graduate School of Science, Tohoku University, 6-3 Aza-Aoba, Aramaki, Aoba-ku, Sendai 980-85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To calibrate the vegetation parameters for orchards, we use a Latin Hypercube approach (Pianosi et al, 2015) to generate 600 parameter sets for m and V c,max . Parameter values are sampled across the uniform distribution of the entire range of values considered reasonable for any vegetation type; for m that range was 4 to 12 and for V c,max that range was 20 to 120 (Göhler et al, 2013; Jefferson et al, 2017; Kattage et al, 2009; Yamazaki et al, 2013). As these parameters are hard coded in the ParFlow.CLM model and the model is computationally demanding, a larger set of parameters was deemed unnecessary.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To calibrate the vegetation parameters for orchards, we use a Latin Hypercube approach (Pianosi et al, 2015) to generate 600 parameter sets for m and V c,max . Parameter values are sampled across the uniform distribution of the entire range of values considered reasonable for any vegetation type; for m that range was 4 to 12 and for V c,max that range was 20 to 120 (Göhler et al, 2013; Jefferson et al, 2017; Kattage et al, 2009; Yamazaki et al, 2013). As these parameters are hard coded in the ParFlow.CLM model and the model is computationally demanding, a larger set of parameters was deemed unnecessary.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that the most sensitive vegetation parameters in CLM control the slope of the relationship between photosynthesis and r s and the carboxylation rate (Göhler et al, 2013;Jefferson et al, 2017;Li et al, 2013) that range was 20 to 120 (Göhler et al, 2013;Jefferson et al, 2017;Kattage et al, 2009;Yamazaki et al, 2013). As these parameters are hard coded in the ParFlow.CLM model and the model is computationally demanding, a larger set of parameters was deemed unnecessary.…”
Section: Model Scenariosmentioning
confidence: 99%
See 1 more Smart Citation